Pengurangan Amonium (NH4) dan Materi Organik (COD) pada Lindi TPA Melalui Sistem Sinambung Anaerob dan Aerob Cultur-Alga - Pieter M. I. Torobi; Christina N. Manuputty; Jubhar C. Mangimbulude (Universitas Sebelas Maret, 2015)
Final Disposal (Landfill) generally produce pollutants such as leachate and can have a negative impact on the environment. In general, leachate in landfill containing high of organic matter and hogh of nitrogen, as well as landfill leachate Ngronggo-Salatiga. The content of COD and ammonium far exceeded the applicable waste water. To reduce the content of organic matter and ammonium in leachate, landfill leachate in Ngronggo can processed using anaerobo-aerobic process (algae culture) is continuous, with a 24-hour contact time to the leachate for one week. The results showed that anaerobic-aerobic system (algae culture) were conducted in a laboratory scale give significant results on the reduction of COD and ammonium to over 90%, and produce refined quality that meets quality standards.Keywords: landfill leachate, algae culture, continuous, anaerobic, aerobic